2003
DOI: 10.1080/01926230390173798
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Ductal Cell Hyperplasia in the Submandibular Salivary Glands of Wistar Rats Chronically Treated with a Novel Steroidal Compound

Abstract: A high incidence of multifocal ductal hyperplasia was observed in the submandibular salivary gland of rats treated for 26 weeks with a high dose of a novel synthetic steroid with combined estrogenic and progestagenic properties. Hyperplastic foci consisted of microcystic duct-like structures lined by a single or multilayered epithelium, sometimes showing a tendency towards a cribiform growth pattern. The hyperplastic ducts were embedded in a collagen-rich stroma and surrounded by numerous myoepithelial cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
2
4
1
Order By: Relevance
“…In the DMSO group, a considerable degree of vacuolation was noted in the acinar structures. These results are similar to that of De Rijk et al (30), who revealed pseudoluminal structures formed by variably sized cells as a result of steroid application for long periods.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the DMSO group, a considerable degree of vacuolation was noted in the acinar structures. These results are similar to that of De Rijk et al (30), who revealed pseudoluminal structures formed by variably sized cells as a result of steroid application for long periods.…”
Section: Discussionsupporting
confidence: 82%
“…This may be explained by the ability of estrogen to induce the mRNA and protein expressions of both EGF and its receptor in rodent uterus. Moreover, production of EGF may be essential for estrogen-induced responses (29,30,33). The increase in EGF levels observed in the present study is not in accordance with previous studies where estrogen has been shown to inhibit EGF expression, suggesting a tissue-specific dual effect (24,(33)(34)(35).…”
Section: Figcontrasting
confidence: 54%
“…Oral dosing of rats with a high dose of a novel synthetic steroid with combined estrogenic and progestagenic properties resulted in multifocal hyperplastic lesions within submandibular salivary glands that originated from intercalated ducts. Additional studies suggested that the specific ratio of estrogenic and progestagenic activity of the steroid compound played an important role in the hyperplasia of intercalated ducts (de Rijk et al, 2003). Non-drugrelated lesions include salivary gland atrophy that can result from duct ligation (Takahashi et al, 2005), liquid diets (Hall and Schneyer, 1964) or denervation (Wells and Peronace, 1967) salivary glands following amputation of the lower incisor teeth (Takeda et al, 1986).…”
Section: Histopathology Findings Associated With Ip Injection Of Salimentioning
confidence: 99%
“…102 Granular cells stain with antisera for epidermal growth factor. 96 The intracellular distribution of epidermal growth factor in acini and ducts has been confirmed in other species including humans. 103 Study of the mouse submandibular gland has shown that both epidermal growth factor and nerve growth factor are released into saliva following the administration of phenylephrine, sympathomimetic amine acting mainly on α receptors and isoprenaline (isoproterenol), a β adrenergic agent.…”
Section: Rodent Salivary Glandsmentioning
confidence: 85%
“…The granules in these duct cells stain particularly well with the chromotrope-aniline blue stain but also orange G and PAS. 96 These granular cells are of special interest because they contain a large number of heterologous biologically active peptides including nerve growth factor, epidermal growth factor, renin, and kallikrinins. 97À99 Epidermal growth factor is secreted in saliva and believed to promote wound healing.…”
Section: Rodent Salivary Glandsmentioning
confidence: 99%